Critical Review of Applying Party Autonomy and Lex Fori in Indonesia's Cross-Border Business PIL Bill - Jilmaini Asuna; Inayah Samir (Damhil Law Journal, 2026)
This research critically examines the application of the party autonomy principle and the lex fori principle in the Draft Law on Indonesian Private International Law (RUU HPI) and its implications for cross-border business transactions. As the first codification of private international law in Indonesia, the RUU HPI systematically regulates the choice of law and jurisdiction, but creates tension between the freedom of the parties and state sovereignty. This normative legal research uses a statutory, conceptual, and comparative approach, with primary legal materials in the form of the RUU HPI, the Rome I Regulation, and related international instruments. The analysis is conducted qualitatively with grammatical, systematic, and teleological interpretations. The results of the research show that in the principle of party autonomy, the RUU HPI recognizes the freedom to choose the law, but restrictions through public policy and lois de police are formulated without clear parameters, thus potentially reducing legal predictability. In the principle of lex fori , the RUU HPI grants broad jurisdiction to Indonesian courts through exclusive jurisdiction and the doctrine of forum non conveniens , but does not explicitly regulate respect for the choice of court agreement of the parties. The imbalance between these two principles risks reducing Indonesia's attractiveness as a dispute resolution forum. This study recommends reformulating the limits of party autonomy with objective criteria, proportional limitations on exclusive jurisdiction, and explicit recognition of the parties' choice of forum to create a balance between freedom of contract and state sovereignty in the HPI Bill.